THE USE OF YOUTUBE VIDEOS TO IMPROVE WRITING SKILLS ON PERSONAL RECOUNT TEXT TO THE EIGHTH GRADE STUDENTS AT SMPN 6 TABANAN - Ni Putu Wulantari; I Wayan Agustina; Ni Made Kristina Yanti (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2022)
This research is intended to improve writing skills on personal recount text by using YouTube videos. The enquiry applied on the eighth grade students of SMPN 6 Tabanan in 2021/2022 academic year. This research was categorized as Classroom Action Research (CAR), while the subject were 31 students. The data were collected by using the techniques of observation, tests, and documentation. This research was conducted in two cycles in which each cycle consisted of planning, action, observation, and reflection. The result indicated that the students seemed to be more motivated in writing their personal recount subsequently after applying YouTube videos. It can be seen by noticing the comparison on the mean values of pre-test to post-test scores. The mean scores of the writing skill before applying YouTube videos was 62.74, while it was improved to 73 after the use of YouTube videos in cycle I. The post-test in cycle II showed that means score raised to 85. It is concluded that YouTube videos could be a suitable advantage on a learning process of personal recount writing skills.